Compras públicas para inovação e offset na aeronáutica militar: o caso C-390 - Sousa, Cairo Humberto da Cruz (2023)
In 2009, a contract was signed for the design and manufacture of a transport and refueling aircraft between the Brazilian Air Force (FAB) and Embraer. The objective is to modernize the FAB fleet with national aircraft. This contract is part of what is known as public procurement for innovation (PPI), that is, the use of the State's purchasing power to generate and maintain technological innovations. The objective of this work is to identify the potential of PPI, especially those with technological compensation agreements, the offsets, related to the FAB's development and acquisition programs as instruments of a public procurement policy for innovation in Brazil. A case study is made of the acquisition of the development and serial production of the Embraer C-390 Millennium aircraft, in order to understand to what extent the FAB has sufficient resources for purchases of this nature to be successful in its innovation objectives. The research methodology was anchored, to enable a qualitative research, in the investigation of the available literature on the examined themes, concerning documents, such as legislation that governs approved purchases in Brazil, contracts and reports of the institutions involved, and the application of a field research based on an interview with agent linked to the project. As the aeronautical and defense industry is intensive in innovation and already has a reasonably well-established cluster in the country, it is considered that there are auspicious possibilities to be captured by using the offset mechanism. Furthermore, it was verified that a significant part of the public investments of the Union are directed to strategic programs of the FAB, which points to the prominence of this type of expense over other possible investment choices, as well as to the expertise developed by the FAB in conducting contracts of PPI. Evidence was found that the offset policy applied to the KC-X and KC-390 programs was not considered a priority by the FAB. As a result, suppliers who have obligations to make counterparts of this nature have experienced relative autonomy in choosing the beneficiaries of the compensation agreements, as well as the offset modalities themselves. The research also found ambiguous effects of PPI on the aeronautical industry. On the one hand, there was some progress in specific segments and at Embraer. On the other hand, it is not possible to say that there was a significant reduction in dependence on foreign technologies.